Diskursus Guru Kristen: Diciptakan untuk Mendidik, Mengajar dan Melayani - Nassa, Grace Son; Masinambow, Yornan; Rompa, Masye; Banfatin, Nahor (MANTHANO: Jurnal Pendidikan Kristen, 2024)
Abstract: This article describe and analyze the Christian teacher discursively, where the Christian teacher is created to educate also teach, and serve. Christian teachers must first understand the theological concepts of creation to redemption as fundamental in educating students. Christian teachers must rely on Christ as a guide for their teaching and education in addition to themselves with various scientific perspectives. In this article, a qualitative research approach with a literature study method is used to describe and analyze Christian teachers. The results found are that Christian teachers in their progress as educators must have biblical insights that are first attached to the teacher and then implemented in students. In addition, Christian teachers need to be creative and effective like Christ who in His teaching attracted the attention of many people, complicated teaching but simplified as best as possible but with the aim of proclaiming the Kingdom of God. The Christian teacher's biblical knowledge and creativity are based on introducing God based on His word to the learners. Christian teachers must upgrade themselves in teaching and educating, not be rigid and follow Christ who taught with power, creativity and effectiveness, in contrast to the scribes who taught as a formality and stuck to legalism. In this way, the Christian teacher's progress is discursively dynamic, meeting the challenges of the times while at the same time adhering to biblical insights based on the teaching of Jesus Christ, the Great Teacher.    Abstrak: Artikel menjabarkan serta menganalisis tentang guru Kristen secara diskursif, dimana guru Kristen dicipta untuk mendidik sekaligus mengajar dan melayani. Guru Kristen harus terlebih dahulu memahami konsep teologis penciptaan hingga penebusan sebagai hal fundamental dalam mendidik para peserta didik. Guru Kristen harus mengandalkan Kristus sebagai pedoman pengajaran dan pendidikannya selain diri mereka sendiri dengan berbagai perspektif keilmuan yang ada. Dalam artikel ini, pendekatan penelitian kualitatif dengan studi kepustakaan digunakan untuk mendeskripsikan serta menganalisis guru Kristen. Adapun hasil yang ditemukan adalah guru Kristen dalam kemajuannya sebagai pendidik harus memiliki wawasan alkitabiah yang terlebih dahulu melekat dalam diri guru lalu diimplementasikan pada peserta didik. Selain itu, guru Kristen perlu kreatif dan efektif seperti Kristus yang dalam pengajaran-Nya yang menarik perhatian banyak orang, pengajaran yang rumit namun disederhanakan sebaik mungkin namun dengan tujuan pewartaan Kerajaan Allah. Wawasan alkitabiah dan kreatifitas guru Kristen didasarkan pada memerkenalkan Allah berdasarkan firman-Nya kepada para peserta didik. Guru Kristen harus mengupgrade diri dalam mengajar dan mendidik, tidak kaku serta mengikuti Kristus yang mengajar dengan berotoritas, kreativitas, dan efektivitas, kontras dengan para ahli Taurat yang mengajar sebagai formalitas dan terjebak pada legalisme. Dengan begitu, kemajuan guru Kristen secara diskursif adalah bergerak dinamis, memenuhi tantangan zaman namun pada saat yang sama berpatokan pada wawasan alkitabiah berdasarkan pada pengajaran Yesus Kristus, Sang Guru Agung.